A quantitative assessment of strategies to achieve the sustainable development goals: An application to Guatemala - Onil Banerjee; Martin Cicowiez; Mark Horridge; Renato Vargas (Inter-American Development Bank (IDB), 2017)
The Sustainable Development Goals (SDGs) are a universal call to action to end poverty and protect the environment. The Government of Guatemala is prioritizing the SDGs it will focus on and defining lines of action to make progress towards achieving them. In this paper, we apply the Integrated Economic-Environmental Modelling platform for Guatemala (IEEM-GUA) to evaluate the economic, environmental and wealth impacts of strategies for achieving the SDGs. We evaluate specific lines of action to achieve the second SDG to achieve food security and promote sustainable agriculture, and; the sixth SDG to achieve water and sanitation coverage for all. We find that significant new investment in these areas would be required to meeting these SDGs and that the overall pace of economic growth is critical. IEEM applied to the SDGs lends transparency and structure to the prioritization and agenda setting process. It sheds light on the need for complementary policies to reconcile lines of action that can inadvertently move progress toward specific SDGs in opposite directions. Finally, an advantage of an integrated framework such as IEEM is its ability to highlight trade-offs, potential win-wins and inter-linkages between SDGs, where one line of action can make progress towards multiple SDGs simultaneously.
Keywords: C6; E01; Q; I3; D61; 330; ex-ante economic impact evaluation; system of environmental-economic accounting; computable general equilibrium model; sustainable development goals; system of national accounting; economic and environmental indicators; wealth; natural capital; ecosystem services